1966
DOI: 10.1021/bi00871a033
|View full text |Cite
|
Sign up to set email alerts
|

Properties of Chromatium Subchromatophore Particles Obtained by Treatment with Triton X-100*

Abstract: Chromatium chromatophores contain bacteriochlorophyll (BChl) in three forms which have absorption maxima around 800, 850, and 890 mix.Treatment with 3% Triton X-100 produces two fragments which can be separated by sucrose densitygradient centrifugation. The lighter fraction contains

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
24
1

Year Published

1968
1968
2015
2015

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(26 citation statements)
references
References 23 publications
1
24
1
Order By: Relevance
“…These earlier preparations probably achieved only partial breakdown of the membraneous structure since all fractions reported are considerably heavier than those presently documented. It is more difficult to relate the present results to other studies where inactive fractions are found (Garcia et al, 1966a(Garcia et al, , 1968bReed and Clayton, 1968;Reed, 1969;Gingras et al, 1968;Thornber et al, 1969). Inactive fractions could arise for any of the following reasons: (a) loss of activity during preparation, (b) lack of redox control during activity assay, or (c) inactive photoreceptor subunits in the original membrane as a result of past mutations affecting the protein with which the trap and/or bulk pigments are associated.…”
Section: Discussioncontrasting
confidence: 60%
See 1 more Smart Citation
“…These earlier preparations probably achieved only partial breakdown of the membraneous structure since all fractions reported are considerably heavier than those presently documented. It is more difficult to relate the present results to other studies where inactive fractions are found (Garcia et al, 1966a(Garcia et al, , 1968bReed and Clayton, 1968;Reed, 1969;Gingras et al, 1968;Thornber et al, 1969). Inactive fractions could arise for any of the following reasons: (a) loss of activity during preparation, (b) lack of redox control during activity assay, or (c) inactive photoreceptor subunits in the original membrane as a result of past mutations affecting the protein with which the trap and/or bulk pigments are associated.…”
Section: Discussioncontrasting
confidence: 60%
“…Successful fractionation and reconstitution (Keilin and King, 1960;Green et al, 1961;Criddle et af., 1962Criddle et af., , 1966Hatefi et al, 1961Hatefi et al, , 1962Kagawa and Racker, 1966;McConnell et af., 1965;Tzagoloff et af., 1967) of mitochondrial systems have stimulated many similar studies with photosynthetic materials (Komen, 1956;Bril, 1958Bril, , 1960Clayton, 1962a,b;Boardman and Anderson, 1964;Anderson and Boardman, 1966;Kok, 1961;Garcia et al, 1966aGarcia et al, ,b, 1968aCusanovich and Kamen, 1968;Reed and Clayton, 1968;Ke et al, 1968;Thornber et al, 1969), and have also given rise to new theories on the structure of membranes. To us the most attractive hypothesis is that supported by Green (Green and Goldberger, 1967) and by Korn (Korn, 1966) which suggests that the entire membrane is formed by association of relatively small proteinlipid subunits.…”
mentioning
confidence: 99%
“…As noted in the Introduction, the reverse ET shown in Reaction 1 is analogous to the reduction of (BChl)2t by Fe(II)cytc (7)(8)(9)(10)(11). This reaction takes 1 ,us at room temperature in Chromatium vinosum (29,30) and has an estimated free energy change of -0.5 eV.…”
Section: Resultsmentioning
confidence: 91%
“…Also, the reverse ET in Zn-Fe(III)Cl to reform the. initial ground state, [Zn+ Fe (11)]CI--Zr-Fe(I)C1, [1] is analogous to the reduction of (BChl2)t by cytochrome c (cytc) in bacterial photosynthesis (7,8), (BChl)2tFe(II)cyt-c --(BChl)2Fe(III)cyt-c. [2] The oxidation of Fe(II)cyt-c is one. of the earliest-studied light-driven ETs associated with the "primary" events of bacterial photosynthesis (9)(10)(11).…”
mentioning
confidence: 99%
“…vinosum (formerly Chromatium (Ch.) vinosum strain D) is a photosynthetic purple sulfur bacterium that possesses the remarkable ability to alter the absorption spectral characteristics of its LH2 complex depending on the environmental conditions under which the organism is grown (Wassink et al 1939;Garcia et al 1966;Hayashi and Morita 1980;Carey et al 2014). With variations in light intensity, temperature or type of reduced sulfur nutrient in the growth media, the position of the 850 nm absorption band can be blue-shifted to either 840 or 820 nm.…”
Section: Introductionmentioning
confidence: 99%